GAMBARAN PERILAKU PENGRAJIN KERUPUK SINGKONG MERAH KHAS BANJAR KOBUN DALAM PENGGUNAAN RHODAMIN B PADA KERUPUK YANG DIPRODUKSI TAHUN 2017 - siti sahara nasution; Jumirah .; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Crackers made from cassava are very easy to find, contained in various shapes, sizes, colors of interest, and a distinctive taste so popular for people, especially children. Industry competition forces manufactures to innovate on their products. However, still many snacks are suspected to use rhodamine B as food coloring. Based on the observations there are cassava crackers with striking red color that often found in the market and school area. The purpose of this research is to find out the description of knowledge and the attitude of crakers maker with the use of rhodamine B dye on the typical red cassava crackers Banjar Kobun. This research is descriptive with cross sectional design. Samples was red cassava crackers maker and sample unit was crackers. The results showed that the knowledge and attitude of craftsmen in the good category about the use of rhodamine B on cracker amounted to 73.3% and 66.7%. However, based on the results of cracker analysis conducted on rhodamin B is known all samples using dye indicated containing rhodamin B. Regional Health Office division of health promotion and National Agency of Drug and Food Control in North Sumatra are expected to make a building and color inspections regularly to red cassava crackers makers typical Banjar Kobun. The Crackers maker should be to use food grade dyes. Keywords : knowledge, attitude, rhodamine B, cassava, crackers maker